KORELASI PERILAKU HIDUP BERSIH DAN SEHAT DENGAN KECACINGAN PADA SISWA SEKOLAH DASAR DI KABUPATEN PROBOLINGGO - Gunawan, Arif; Mindiharto, Sestiono (Jurnal Kesehatan Masyarakat Indonesia, 2024)
Background: Soil-transmitted worms are still a health problem in Probolinggo Regency, especially related to clean and healthy living behavior. Health and hygiene education is an effort to reduce worm transmission and infection. The purpose of this study was to identify clean and healthy living behaviors related to worms. Method: The study design was observational analytic with a Cross-Sectional Study approach. The population was elementary school students in Probolinggo Regency with a sample size of 607 students taken by cluster sampling with a single-stage method. Identification was carried out on clean and healthy living behaviors and the number of worm eggs in feces and soil. Data analysis used Chi Square with an alpha of 0.05. Results: The data showed that 96.4% of respondents were negative and 3.6% were positive with a distribution of worm eggs of 2.1% Ascaris lumbricoides, 1.3% Hookworm and 0.5% Trichuris trichiura with mild infection intensity. The results of the Chi Square test showed no relationship between washing hands before eating, washing hands after defecating, wearing footwear, and nail conditions with worms in students with p values of 0.748, 0.584, 0.550, 0.777, respectively. Conclusion: These results are due to the history of exposure and the body's immunity in overcoming parasite invasion. Long exposure to children with positive worms will make the parasite colony maintain a clean and healthy lifestyle. Conversely, low exposure and strong immunity keep children free from worm infections.